2016
DOI: 10.1016/j.forc.2016.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring compositional changes of the lipid fraction of fingermark residues deposited on paper during storage

Abstract: 3Characterising the changes in fingermark composition as a function of time is of great value for 4 improving fingermark detection capabilities by understanding the processes and circumstances under 5 which target compounds become degraded. In this study, gas chromatography-mass spectrometry 6 was used to monitor relative changes in the lipids from latent fingermarks over 28 days. Principal 7 component analysis of the relative composition of 15 lipids in fingermarks showed that fingermark 8 age was a significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…Light exposure has been linked to increased degradation rates of fingermark compounds such as squalene. 5,27 However, Pleik et al inferred that the accelerated ozonolysis of monounsaturated TGs in samples exposed to light might instead be due to competing degradation mechanisms and additional environmental factors such as increased exposure to air flow. 13 Similar observations were made by Hinners et al who noted that the rate of TG ozonolysis was significantly reduced when fingermarks were stored in both clear and opaque containers, compared to samples left exposed to ambient air.…”
Section: Changes In Glyceride Profile With Sample Agementioning
confidence: 99%
See 2 more Smart Citations
“…Light exposure has been linked to increased degradation rates of fingermark compounds such as squalene. 5,27 However, Pleik et al inferred that the accelerated ozonolysis of monounsaturated TGs in samples exposed to light might instead be due to competing degradation mechanisms and additional environmental factors such as increased exposure to air flow. 13 Similar observations were made by Hinners et al who noted that the rate of TG ozonolysis was significantly reduced when fingermarks were stored in both clear and opaque containers, compared to samples left exposed to ambient air.…”
Section: Changes In Glyceride Profile With Sample Agementioning
confidence: 99%
“…The rapid oxidation of squalene, a highly unsaturated compound, has been observed in many investigations into fingermark lipid degradation. [4][5][6]16,18,27 The rate of squalene loss is accelerated by light exposure. 5,27 Cholesterol has been shown to decrease at a slower rate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The bulk chemical composition of fingermarks has been extensively studied, revealing that the composition of fingermarks is complex (many chemical species present), 2,8,28,29 varied (composition is influenced by the donor, 2,20,29,30 the substrate 1,31 and the environment); 3,4,15,20 and dynamic (composition changes over time). [2][3][4]32 Despite this complexity, the chemical components of fingermarks can be broadly divided into 3 categories: sebaceous material (lipophilic chemical compounds), eccrine material (hydrophilic chemical compounds), and debris such as skin cells or exogenous particles (cosmetics, dirt, etc.). Typical sebaceous, eccrine and debris components of fingermarks are presented in Tables 3 and 4.…”
Section: Resultsmentioning
confidence: 99%
“…The amount of squalene in fingermarks (obtained by GC-MS) was used as a marker of homogeneity when comparing uncontrolled and controlled deposition protocols [ 207 ]. Lipid composition and aging : The compositional changes of the lipid fraction of sebum-rich fingermarks left on paper was monitored using GC-MS [ 208 ]. By observing the relative composition of 15 lipids over 28 days, the authors confirmed previously-established trends (e.g., squalene degradation, intra- and inter-variability) and emphasized the impact of storage conditions, the dynamic of degradation, as well as the persistence of free fatty acids and wax esters over time.…”
Section: Fingermark Composition and Detectionmentioning
confidence: 99%